Perceptions of Small-Scale Farmers on Tobacco Contract Farming: The Case of Marondera Rural District, Zimbabwe - Ruzhani, Freddy; Abbyssinia, Mushunje (Journal of Economics and Behavioral Studies, 2022)
Small-scale farmers’ perceptions of tobacco contract farming schemes in the Marondera rural district of Zimbabwe were critically assessed in this paper. The multi-stage sampling design was used to select five wards with the highest number of tobacco contracted farmers from where 60 contract and 60 non-contract tobacco farmers were randomly selected. A 5-point Likert scale was used to rank farmers’ perceptions. The paper established that small-scale farmers in Marondera rural district strongly believe contract farming makes it possible for the majority of farmers to venture into the production of high-value crops as it provides access to the much-needed markets while reducing the risk of price fluctuations. However, the majority of the respondents believed that contract farming is not profitable and there is a manipulation of farmers in contract farming arrangements. The independent samples t-test indicated a significant difference in perception score between participants and non-participants of tobacco contract farming schemes (p<0.05). The farmers who were not participating in tobacco contract farming schemes had a more positive perception of these schemes while those who participated had a more negative perception. The major implication is that gains associated with tobacco contract arrangements are not always apparent to farmers while the disincentives may be more visible. It is therefore fundamental that contract companies address some of the shortcomings existing in these contractual arrangements as well as change the perception of the farmers to develop mutually beneficial lasting relationships with their major stakeholders.